Contribution of Different Positron Emission Tomography Tracers in Glioma Management: Focus on Glioblastoma - Moreau, Aurélie; Febvey, Olivia; Mognetti, Thomas; Frappaz, Didier; Kryza, David (Frontiers in Oncology, 2019)
Although rare, glioblastomas account for the majority of primary brain lesions, with a dreadful prognosis. Magnetic Resonance Imaging (MRI) is currently the imaging method providing the higher resolution. However, it does not always succeed in distinguishing recurrences from nonspecific post-therapeutic-related changes caused by the combination of radiotherapy, chemotherapy and targeted therapy, also called pseudoprogression. Strenuous attempts to overcome this issue is highly required for these patients with a short life expectancy, for both ethical and economic reasons. Additional reliable information may be obtained from positron emission tomography (PET) imaging. The development of this technique along with the emerging of new classes of tracers can help in diagnosis, prognosis and assessment of therapies. We reviewed the current data about the commonly used tracers such as 18F-Fluorodeoxyglucose (18F-FDG) and radiolabeled amino-acids, as well as different PET tracers recently investigated to report their strengths, limitations and their relevance in glioblastoma management.